Comparing meat and meat alternatives: an analysis of nutrient quality in five European countries - Thies Petersen; Stefan Hirsch (Cambridge University Press, 2023)
Abstract Objective: To assess and compare the (macro-)nutritional composition of red meat (RM) and poultry meat (PM) products with the emerging category of meat substitutes. Design: We use information on nutritional values per 100 g to estimate the differences in the nutritional composition between RM, PM, vegan meat substitute (VMS) and non-vegan meat substitute (NVMS) and derive six unique meat product clusters to enhance the comparability. Setting: Meat markets from five major European countries: France, Germany, UK, Italy and Spain. Participants/Data: Product innovation data for 19 941 products from Mintel's Global New Product Database from 2010 to 2020. Results: Most of the innovations in the sample are RM products (55 %), followed by poultry (30 %), VMS (11 %) and NVMS (5 %). RM products exhibit a significantly higher energy content in kcal/100 g as well as fat, saturated fat, protein and salt all in g/100 g than the meatless alternatives, while the latter contain significantly more carbohydrates and fibre than either poultry or RM. However, results differ to a certain degree when products are grouped into more homogeneous clusters like sausages, cold cuts and burgers. This indicates that general conclusions regarding the health effects of substituting meat with plant-based alternatives should only be drawn in relation to comparable products. Conclusions: Meat substitutes, both vegan and non-vegan, are rated as ultra-processed foods. However, compared with RM products, they and also poultry products both can provide a diet that contains fewer nutrients-to-limit, like salt and saturated fats.